Development Control And Vulnerable Coastal Lands: Examples Of Australian Practice - Robb, A.; Payne, M.; Stocker, L.; Middle, Gary; Trosic, A. (Routledge, 2018)
© 2018, © 2018 Editorial Board, Urban Policy and Research. A range of regulatory instruments can be used to modify development-control frameworks for the purposes of adapting urban areas to climate change-induced coastal erosion and inundation. This article investigates the approach of three local governments across Australia. It finds that local governments are modifying development-control frameworks to ensure the appropriate development of vulnerable coastal lands. However, the article also demonstrates the limitations in relying on development control to achieve adaptation objectives such as preserving public beach amenity, and highlights the need for legislative reform or the emergence of incentive-based instruments to complement development control.